Numerical-based smeared stiffener method for global buckling analysis of grid-stiffened composite cylindrical shells. (15th September 2016) - Wang, Bo; Tian, Kuo; Hao, Peng; Zheng, Yanbing; Ma, Yunlong; Wang, Jiebing
Abstract: With regard to future heavy-lift launch vehicles, the buckling analysis and optimization of large-scale stiffened shells by finite element method (FEM) suffer from unbearable computational cost. In spite of the high analysis efficiency, the traditional smeared stiffener method (SSM) is still not accurate enough owing to the assumptions of analytical derivations. In this study, an effective and efficient numerical-based smeared stiffener method (NSSM) is proposed for the buckling analysis of stiffened shells. Firstly, the representative unit cell of stiffened shell is divided, and then it is equivalent using a novel numerical implementation of asymptotic homogenization (NIAH) method. The equivalent stiffness coefficients can be obtained accurately. Then, the buckling load is calculated by means of Rayleigh–Ritz method. Comparing with the prediction results of SSM and FEM, the high prediction accuracy and efficiency of NSSM are observed. Then, the effectiveness of NSSM for different loading conditions and model scales are discussed. Finally, numerical examples illustrate the high prediction accuracy and widespread applicability of NSSM for various grid-patterns, and the advantage of the rotated triangle grid-pattern in load-carrying capacity among various grid-patterns is demonstrated.